Analytic peculiarities of the polaron mass operator in the first two orders of the coupling constant - Tkach, M.; Voitsekhivska, O.; Val', O. (Condensed Matter Physics, 1998)
The exact analytic expression for the polaron mass operator in the second order of the coupling constant is established for the first time. It holds in the whole energy scale. The peculiarities of the mass operator are analysed. The renormalized polaron energy spectrum is obtained and analysed in this approximation. Вперше отримано точний аналітичний вираз для масового оператора полярона у другому порядку за константою зв’язку, справедливий для всієї області енергій. Проаналізовано особливості масового оператора. Знайдено і проаналізовано перенормований енергетичний спектр полярона у цьому наближенні.